Woakes' syndrome: Report of a rare case - Amar Hazwan1; Shi Nee T1; 2; Syed Zaifullah Syed Hamzah1; 3 (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Chronic rhinosinusitis (CRS) with or without nasal polyp is one of the most prevalent disease affecting worldwide [1]. This disease cause a signifi cant impact n a person quality of life, with the severity of symptoms comparable to those with debilitating diseases such as diabetes mellitus, congestive heart failure, chronic obstructive pulmonary disease [2]. Woakes' syndrome, fi rst described by Woakes in 1885 which is also better known as ethmoiditis, is a rare condition causing disfi gured facial appearance by extensive nasal polyposis growth in the nasal cavity and paranasal sinuses [3]. It was further elaborated by Société Française de Laryngology withe the following characteristics; deformed nasal pyramid due to hypertrophic process, ethmoiditis, childhood disease of bilateral nasal polyps in the middle meatus and failure in treatment with recurrences [3,4].